Aerogel-porous carbon sphere composite material as well as preparation method and application thereof
Through the multi-stage pore structure and mesoporous design of aerogel-porous carbon ball composite material, the problem of low nicotine removal efficiency in flue gas in the prior art is solved, and the problem of low nicotine removal in flue gas is achieved. Efficient removal of nicotine and 3-vinylpyridine and improves the mechanical properties of the material.
Patent Information
- Application Number
- CN202411522253.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art has problems with poor adsorption performance and lack of targeting in removing nicotine from ambient flue gas, making it difficult to effectively remove nicotine.
Using aerogel-porous carbon ball composite material, the multi-stage porous structure and mesoporous structure are formed by combining porous carbon balls with sodium polyacrylate aerogel and polyvinyl alcohol aerogel, using π-π conjugation and hydrogen bonding. Effects to improve adsorption efficiency.
It achieves efficient removal of nicotine and 3-vinylpyridine, improves the removal rate of environmental flue gas purification materials, and gives the material strong mechanical properties and easy processability.
Smart Images

Figure CN119186522A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of porous adsorption materials, and in particular to an aerogel-porous carbon sphere composite material and a preparation method and application thereof. Background Art
[0002] Environmental smoke is a type of substance produced in indoor air due to smoking tobacco products, mainly including sidestream smoke released from the combustion cone between two puffs and mainstream smoke exhaled by smokers. The indicators of concern for environmental smoke generally include VOCs, formaldehyde, nitrogen oxides and nicotine. VOCs, formaldehyde and nitrogen oxides are common indoor pollutants and atmospheric pollutants, while nicotine is a relatively unique compound, which mainly exists in the form of gas phase in environmental smoke. Using an air purifier is a common means of purifying environmental tobacco smoke. At present, the research and development of air purification technology at home and abroad mainly focuses on physical adsorption and chemical catalysis. The commonly used functional materials for physical adsorption include activated carbon, zeolite molecular sieves, organic silica and fibers, and the chemical catalysis mainly involves photocatalytic oxidation. In general, in terms of indoor air purification, the current large-scale industrial use is mainly physical adsorbents such as activated carbon and molecular sieves, which mainly target conventional air pollutants such as VOCs, but lack specificity for nicotine.
[0003] When cigarette smoke is transmitted in the filter, nicotine exists in both the gas phase and the particle phase. As the smoke is further transmitted in the filter, the proportion of nicotine in the particle phase gradually increases, and finally exists in the mainstream smoke in the particle phase. Therefore, the removal of nicotine by cigarette filter additives is mainly achieved through physical collision, interception, diffusion, physical adsorption, etc. For example, Yuan Shuxia et al. used nitric acid-modified activated carbon in cigarette filters, and the adsorption capacity of nicotine and tar increased by 25.6% and 8.8% respectively (Effect of Activated Carbon Modification on Filter Adsorption Performance [J], Journal of Taiyuan University of Technology, 2007, 38 (6): 509-512). For example, Wang Chenhui et al. investigated the effect of melon rings on the retention of nicotine in mainstream cigarette smoke. When the dosage of melon rings was 20 mg, the retention of tar and nicotine was 46.1% and 60.3%, respectively (Study on the Retention Effect of Melon Rings on Tar and Nicotine in Mainstream Cigarette Smoke [J], Journal of Guizhou University, 2012, 29 (2): 16-19).
[0004] However, nicotine mainly exists in the form of gas phase in environmental smoke. Using existing cigarette filter additives to remove nicotine has problems such as poor adsorption performance and lack of targeting, making it difficult to effectively remove nicotine in environmental smoke. Therefore, it is extremely necessary to develop a material for removing nicotine from environmental smoke. Summary of the invention
[0005] In view of this, the main purpose of the present invention is to provide an aerogel-porous carbon sphere composite material and a preparation method and application thereof, which can effectively remove nicotine in environmental smoke.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: An aerogel-porous carbon ball composite material comprises porous carbon balls, sodium polyacrylate aerogel and polyvinyl alcohol aerogel, wherein adjacent porous carbon balls are connected by the sodium polyacrylate aerogel and the polyvinyl alcohol aerogel to form pores, the porous carbon balls are mainly composed of schisandra carbon balls, dodder carbon balls, mustard carbon balls and scutellaria carbon balls in a mass ratio of 1.5:(0.5-1.5):(1-2):(0.5-1.5), the sodium polyacrylate aerogel is mainly prepared with terephthalate dicarboxylate and sodium polyacrylate as raw materials, the polyvinyl alcohol aerogel is mainly prepared with metal salt and polyvinyl alcohol as raw materials, and the mass ratio of porous carbon balls: sodium polyacrylate: terephthalate dicarboxylate: polyvinyl alcohol: metal salt is 100:(10-20):(0.5-1):(10-20):(5-15).
[0007] The porous carbon sphere has a multi-level pore structure with a pore size distribution range of 0.5-100 nm, providing a path for environmental smoke transmission, and having a strong physical adsorption function for environmental smoke such as nicotine. At the same time, the macroporous structure contains aerogel, which has a chemical adsorption function for substances containing pyridine rings in environmental smoke such as nicotine and 3-vinylpyridine. Some unsaturated bonds on the carbon sphere can produce π-π conjugation with the pyridine rings on components such as nicotine and 3-vinylpyridine in environmental smoke, and the -OH, -COOH and nitrogen-containing groups on the surface of the carbon sphere can produce hydrogen bonds with N heterocyclic rings in components such as nicotine and 3-vinylpyridine, effectively removing components such as nicotine and 3-vinylpyridine.
[0008] The particle sizes of the impatient carbon balls, dodder carbon balls, stir-fried mustard carbon balls and tili carbon balls in the porous carbon balls are 1.7-2.5 mm, 0.8-1.2 mm, 1.2-1.7 mm, and 0.2-0.8 mm, respectively. The four carbon balls have different particle sizes and pore sizes, and cooperate with each other to improve the volume share and specific surface area of the porous carbon balls in the composite material. Preferably, the porous carbon balls are composed of impatient carbon balls with a particle size of 1.8-2.2 mm, dodder carbon balls with a particle size of 0.8-1.2 mm, stir-fried mustard carbon balls with a particle size of 1.2-1.6 mm, and tili carbon balls with a particle size of 0.3-0.7 mm, and the mass ratio of the four is preferably 1.5:1.5:1:1, so that the four carbon balls cooperate with each other, and the volume share and specific surface area of the porous carbon balls in the composite material can be further improved, which is conducive to improving the removal rate of environmental smoke.
[0009] The sodium polyacrylate and polyvinyl alcohol are used as a two-phase aerogel to form mesopores and some micron-sized pores in the aerogel-porous carbon ball composite material, and the mesopores and micron-sized pores have strong physical adsorption. At the same time, the aerogel has strong mechanical properties after molding, which is convenient for the processing and application of purification materials. Therefore, in order to make the aqueous solution of sodium polyacrylate and polyvinyl alcohol as aerogel have a suitable viscosity, the molecular weight of sodium polyacrylate is preferably 2-3 million, and the polyvinyl alcohol is preferably polyvinyl alcohol 0588.
[0010] If the amount of sodium polyacrylate is too low, the cross-linking structure of the aerogel may be loose, the pores may be too large, the ambient smoke may diffuse too quickly, which is not conducive to the adsorption of ambient smoke such as nicotine and 3-vinyl pyridine, and the mechanical properties and stability are not high; if the amount of sodium polyacrylate is too high, the pore structure of the aerogel may be dense, which is not conducive to the growth of polyvinyl alcohol aerogel and the diffusion of ambient smoke such as nicotine and 3-vinyl pyridine, and the removal efficiency is affected. The mass ratio of the porous carbon sphere to sodium polyacrylate is preferably 100: (10-20).
[0011] If the amount of polyvinyl alcohol is too large, it is easy to cause the pore size in the aerogel-porous carbon ball composite material to be too small, the pores are too compact, which is not conducive to the diffusion of environmental smoke components such as nicotine and 3-vinyl pyridine in the material pores; if the amount of polyvinyl alcohol is too small, it is easy to obtain a disordered and loose network structure, and the environmental smoke diffuses too fast, which is not conducive to the adsorption of environmental smoke such as nicotine and 3-vinyl pyridine. At the same time, the structural stability of the aerogel is poor, and the mechanical properties are not high, which easily causes the pore structure to collapse. Therefore, the mass ratio of the porous carbon ball to sodium polyacrylate is preferably 100: (10-20).
[0012] The terephthalate dicarboxylate can be disodium terephthalate, dipotassium terephthalate, disodium terephthalate, 1-sodium formate-4-sodium acetate-benzene, etc., because it contains benzene rings and carboxyl groups, the benzene rings can increase the conjugated interaction between the composite material and environmental smoke components such as nicotine and 3-vinyl pyridine, and the carboxyl group can be complexed with the metal ions in the subsequent metal salt. If the amount of terephthalate dicarboxylate is too small, it is difficult to achieve the effect of removing environmental smoke components such as nicotine and 3-vinyl pyridine; if the amount is too much, it will affect the mechanical properties of the aerogel, so the mass ratio of the porous carbon spheres to the terephthalate dicarboxylate is preferably 100: (0.5-1).
[0013] The metal salt can be a soluble iron salt, a soluble copper salt, a soluble nickel salt, etc., such as iron nitrate, copper nitrate, iron sulfate (Fe2(SO4)3), copper sulfate, iron chloride (FeCl3), copper chloride, etc., wherein the metal ions have unsaturated metal sites, which can be complexed with environmental smoke components such as nicotine and 3-vinylpyridine. Therefore, if the amount of metal salt is too small, it will affect the effect of gas-phase nicotine removal; if the amount is too large, it will affect the structure of the aerogel and easily lead to poor structural mechanical properties. Therefore, the mass ratio of the porous carbon spheres and the metal salt is preferably 100: (5-15), and the molar ratio of the metal ions in the metal salt to the total carboxylates in the sodium polyacrylate and terephthalate dicarboxylate is preferably 1:2 to 1:3.
[0014] The present invention also provides a method for preparing the above-mentioned aerogel-porous carbon sphere composite material, comprising the steps of: S1. Prepare a single-phase aerogel-porous carbon sphere composite material: mix the carbon spheres of schizonepeta tenuifolia, carbon spheres of dodder seeds, carbon spheres of stir-fried mustard seeds and carbon spheres of scutellaria baicalensis seeds and fill a mold, then pour a first gel aqueous solution into the mold until all the carbon spheres therein are just immersed, stand for aging, and freeze-dry to obtain a single-phase aerogel-porous carbon sphere composite material in the mold, wherein the first gel aqueous solution is an aqueous solution of a uniform mixture of terephthalate dicarboxylate and sodium polyacrylate; S2. Preparation of a dual-phase aerogel-porous carbon sphere composite material: pouring a second gel aqueous solution into the mold so that the second gel aqueous solution just completely immerses the single-phase aerogel-porous carbon sphere composite material, allowing it to stand for aging, freeze-drying, and demolding to obtain a dual-phase aerogel-porous carbon sphere composite material; wherein the second gel aqueous solution is an aqueous solution of a uniform mixture of metal salts and polyvinyl alcohol.
[0015] In the step S1, after static aging, the first gel aqueous solution is filled in the gaps between adjacent porous carbon balls, and after freeze-drying, water in the first gel aqueous solution sublimates to form a porous structure, thereby obtaining a single-phase aerogel-porous carbon ball composite material in the mold. After the single-phase aerogel-porous carbon ball composite material is obtained, it does not need to be demolded and can be directly used in the next step.
[0016] The concentration of sodium polyacrylate in the first gel aqueous solution cannot be too high. If it is too high, it may lead to a denser pore structure of the aerogel, which is not conducive to the growth of polyvinyl alcohol aerogel and the diffusion of components such as nicotine and 3-vinyl pyridine, affecting its adsorption efficiency. If the concentration of sodium polyacrylate is too low, it cannot effectively connect adjacent porous carbon spheres or the connection density is low. Even after the subsequent growth of polyvinyl alcohol aerogel, its pores may still be too large, which is not conducive to the adsorption of environmental smoke, and the mechanical properties and stability are not high. Therefore, the mass percentage concentration of sodium polyacrylate is preferably 5%-10%; the mass percentage concentration of terephthalate is 0.25-0.5%, and the mass ratio of the first gel aqueous solution to the carbon spheres therein is preferably (1.8-2.2): 1.
[0017] In the process of preparing the single-phase aerogel-porous carbon sphere composite material in step S1, the preparation method of the first gel aqueous solution includes: slowly adding terephthalate and sodium polyacrylate to water in sequence, mechanically stirring until completely dissolved, and removing bubbles by ultrasound to obtain the first gel aqueous solution. In this step S1, the static aging time is preferably 12-24 hours.
[0018] The cuscuta carbon balls, dodder carbon balls, stir-fried mustard carbon balls and scutellaria carbon balls are all activated carbons, and are all prepared by existing activated carbon preparation methods, such as physical activation method, chemical activation method and the like.
[0019] In step S2, after standing and aging, the second gel aqueous solution is filled in the gaps between adjacent porous carbon balls. After freeze-drying, the water in the second gel aqueous solution sublimates to form a porous structure, thereby forming a dual-phase aerogel-porous carbon ball composite material. The concentration of sodium polyacrylate in the second gel aqueous solution cannot be too high. If it is too high, it may cause the pore structure of the aerogel to be dense, which is not conducive to the diffusion of nicotine and affects its removal efficiency; if the concentration of polyvinyl alcohol is too low, the pores may be too large, which is not conducive to the adsorption of environmental smoke, and the mechanical properties and stability are not high. Therefore, the mass percentage concentration of polyvinyl alcohol is preferably 5.5%-10.0%; the mass percentage concentration of metal salt is 3%-8.5%, preferably 6%-7.5%; the mass ratio of the second gel aqueous solution to the carbon balls therein is (1.75-1.90): 1.
[0020] The preparation method of the second gel aqueous solution comprises: slowly adding metal salt and polyvinyl alcohol to a certain amount of water in sequence, mechanically stirring until completely dissolved, and removing bubbles by ultrasound to obtain the second gel aqueous solution. In the step S2, the static aging time is preferably 12-24 hours.
[0021] The two-step method for introducing the two-phase aerogel in the present invention is mainly to prevent the carboxyl groups in the first-phase sodium polyacrylate aerogel and terephthalate from complexing with the metal ions in the metal salt in advance, which is not conducive to the formation of gel; the two-phase aerogel is introduced in two steps, firstly preparing the sodium polyacrylate aerogel containing terephthalate, then dissolving the metal salt and polyvinyl alcohol in water in sequence to form a second gel aqueous solution containing metal ions, and then pouring the second gel aqueous solution containing metal ions into and immersing the single-phase aerogel-porous carbon sphere composite material prepared in step S1, wherein a small part of the metal ions are complexed with the carboxyl groups, while most of the metal ions are in the second-phase aerogel, so that metal active sites are introduced into the prepared composite material, which is conducive to complexing with environmental smoke components such as nicotine and 3-vinylpyridine.
[0022] According to tests, the saturated adsorption capacity of nicotine and 3-vinylpyridine of 1 gram of aerogel-porous carbon ball composite material is above 60 mg / g and above 50 mg / g, respectively. The saturated adsorption capacity of nicotine is preferably 65-280 mg / g, and more preferably 155-255 mg / g; the saturated adsorption capacity of 3-vinylpyridine is preferably 55-230 mg / g, and more preferably 125-205 mg / g.
[0023] Therefore, the present invention also provides a use of the above-mentioned aerogel-porous carbon sphere composite material in preparing a nicotine adsorption material.
[0024] The present invention also provides an application of the aerogel-porous carbon sphere composite material in preparing a 3-vinylpyridine adsorption material.
[0025] The present invention also provides an application of the above-mentioned aerogel-porous carbon sphere composite material in the preparation of an environmental smoke purification material. The aerogel-porous carbon sphere composite material as an environmental smoke purification material can adsorb components such as nicotine and 3-vinyl pyridine in environmental smoke, effectively improving the removal rate of gas-phase nicotine and 3-vinyl pyridine.
[0026] The main reasons why the above-mentioned aerogel-porous carbon ball composite material provided by the present invention can be used as an environmental flue gas purification material are as follows: (1) Physical adsorption: The four porous carbon spheres, namely, Aconitum caryophyllus carbon spheres, Cuscuta australis carbon spheres, Mustard seed carbon spheres and Lepidium tiliaceum carbon spheres, have rich pore structures. The dual-phase aerogel produced by sodium polyacrylate and polyvinyl alcohol further endows the purification material with rich mesopores and some micron-scale pores, which can fully expose more active sites and have strong physical adsorption properties, and can effectively adsorb environmental smoke components such as nicotine and 3-vinylpyridine.
[0027] (2) Chemical adsorption: The four carbon spheres are rich in oxygen functional groups such as -C=O, -OH, -COOH, COC, and nitrogen-containing groups. Some unsaturated bonds can produce conjugated effects with environmental smoke components such as nicotine and 3-vinylpyridine. The -OH, -COOH and nitrogen-containing groups on the surface of the carbon spheres can produce hydrogen bonds with the N heterocyclic rings in components such as nicotine and 3-vinylpyridine, respectively, and can effectively adsorb nicotine and 3-vinylpyridine. The benzene ring of terephthalate increases the conjugated interaction between the purification material and nicotine and 3-vinylpyridine; there are unsaturated metal sites in the composite material, which can be complexed with components such as nicotine and 3-vinylpyridine.
[0028] (3) Material mechanical properties: The carbon balls of Aconitum carmichaelii, Cuscuta australis, Mustard seeds and Lepidium tiliaceum are loose materials as the original biomass activated carbon, which is not conducive to practical application. The present invention combines the four kinds of biomass activated carbon carbon balls of different types and / or particle sizes with two-phase aerogel to prepare aerogel-porous carbon ball composite material, which not only retains the high adsorption characteristics of biomass activated carbon, but also gives the composite material strong mechanical properties and chemical adsorption characteristics due to the introduced two-phase aerogel, making it easy to shape and process.
[0029] Therefore, the specific surface area of the aerogel-porous carbon sphere composite material provided by the present invention is 200-500 m 2 / g, pore volume 0.08-0.185 cm 3 / g, an average pore size of 7-10.5 nm, and has strong physical and chemical adsorption properties for components such as nicotine and 3-vinylpyridine. It can be used as an adsorption material for nicotine and 3-vinylpyridine, efficiently adsorbing nicotine and 3-vinylpyridine, and can also be used as an environmental smoke purification material, which can effectively remove components such as nicotine and 3-vinylpyridine in environmental tobacco smoke. In addition, the aerogel-porous carbon ball composite material of the present invention can be applied to air purification systems, intelligent smoking room purification systems and other scenarios due to its good raw material adjustability, strong controllability of the preparation process, good structural design, strong material synergy, controllable morphology, adjustable size, high mechanical properties, and strong universality. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A schematic diagram of the structure of the aerogel-porous carbon sphere composite material provided in Example 1 of the present invention; Figure 2 Schematic diagram of the preparation process of the aerogel-porous carbon sphere composite material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0032] The terms used in the present invention are all commonly used terms in the relevant field. The raw materials, equipment, preparation processes, testing methods, etc. used are all prior arts in the relevant field unless otherwise specified.
[0033] Examples 1-7 Examples 1-7 of the present invention each provide an aerogel-porous carbon sphere composite material, see Figure 1 Each aerogel-porous carbon ball composite material includes porous activated carbon balls from Cuscuta australis with a particle size of 1.8-2.2 mm and an average pore size of 4.5 nm, porous activated carbon balls from Cuscuta australis with a particle size of 0.8-1.2 mm and an average pore size of 3.7 nm, porous activated carbon balls from Mustard seeds with a particle size of 1.2-1.6 mm and an average pore size of 4.0 nm, and porous activated carbon balls from Lepidium sativum with a particle size of 0.3-0.7 mm and an average pore size of 3.2 nm. Adjacent porous carbon balls are connected by sodium polyacrylate aerogel and polyvinyl alcohol aerogel to form pores, and the macroporous structure in the porous carbon balls is filled with a small amount of sodium polyacrylate aerogel and polyvinyl alcohol aerogel.
[0034] See also Figure 2 The above-mentioned aerogel-porous carbon sphere composite material preparation method comprises the following steps: (1) Preparation of porous carbon spheres Screen the full-grained schisandrae, dodder seeds, mustard seeds and scutellariae seeds, wash them with clean water, and then dry them in an oven at 60℃ until the moisture content is about 5%. The existing activated carbon preparation method (Tian Huayu, Liu Huan, Wang Guorui, et al. Preparation and adsorption performance of activated carbon from spiny bamboo [J]. Journal of Zhejiang A&F University, 2024, 41(02): 429-436) was used to prepare the corresponding porous carbon spheres using four natural plant materials as raw materials.
[0035] (2) Preparation of single-phase aerogel-porous carbon sphere composites Mix the porous carbon balls of Fructus Aconitum, Fructus Cuscutae, Fructus Mustardi and Fructus Lepidopterae at a ratio of 1.5:1:1.5:1, weigh 100 g of the mixed porous carbon balls and put them into a 10 cm × 5 cm × 5 cm rectangular mold. Slowly add disodium terephthalate and sodium polyacrylate into water in turn, stir mechanically until completely dissolved, and remove bubbles by ultrasound to form a first gel aqueous solution. Pour the first gel aqueous solution into the aforementioned mold containing porous carbon balls, and the aqueous solution just immerses all the carbon balls. Stand aging for 12 h, freeze-dry, and obtain a single-phase aerogel-porous carbon ball composite material. Do not demold it and set aside.
[0036] (3) Preparation of dual-phase aerogel-porous carbon sphere composites Slowly add ferric chloride and polyvinyl alcohol into water, stir mechanically until completely dissolved, remove bubbles by ultrasound to form a second gel aqueous solution, pour the second gel aqueous solution into the mold containing the single-phase aerogel-porous carbon sphere composite material, and the aqueous solution just immerses the material completely. Stand and age for 12 hours, freeze-dry, and demold to obtain a two-phase aerogel-porous carbon sphere composite material. The amount of materials used in each embodiment is shown in Table 1.
[0037] Table 1 Material dosage of the examples (unit: g) Comparative Examples 1-8 each provide an aerogel composite material, the preparation method of which is substantially the same as that of Example 1, 2 or 7, with the main differences being as follows: Comparative Example 1: The amount of sodium polyacrylate in step 2 of Example 1 was adjusted to 6.0 g, and the amount of water was adjusted to 193.5 g, and the other conditions were consistent with those of Example 1; Comparative Example 2: The amount of polyvinyl alcohol in step 3 of Example 7 was adjusted to 21.5 g, the amount of water was adjusted to 144.2 g, and the other conditions were consistent with those of Example 7; Comparative Example 3: The amount of ferric chloride in Example 1 was adjusted to 5.6 g, the amount of water was adjusted to 173.5 g, and the other conditions were consistent with those in Example 1; Comparative Example 4: The dodder seed is removed from the four porous carbon spheres in Example 1, and the total mass of the remaining three porous carbon spheres of Cuscuta australis, mustard seed, and scutellaria baicalensis is 80 g. The amount of water in steps (2) and (3) is adjusted to 209.5 g and 193.1 g, respectively. The other conditions are the same as those in Example 1. Comparative Example 5: The stir-fried mustard seeds and scutellaria seeds in the four porous carbon spheres in Example 1 are removed, and the total mass of the remaining two porous carbon spheres of scutellaria and dodder seeds is 50 g. The amounts of water in steps (2) and (3) are adjusted to 239.5 g and 223.1 g, respectively. The other conditions are the same as those in Example 1. Comparative Example 6: The second aerogel in Example 2 was omitted, and other conditions were consistent with those in Example 1; Comparative Example 7: The first aerogel in Example 2 was omitted, and other conditions were consistent with those in Example 1; Comparative Example 8: The four porous carbon spheres in Example 2 were omitted, and other conditions were consistent with those in Example 1.
[0038] The pore structures of the composite materials provided in Examples 1-7 and Comparative Examples 1-8 were analyzed using a specific surface area and pore size tester. The specific data are shown in Table 2.
[0039] Table 2 Pore structure of aerogel composites It can be seen from Table 2 that the specific surface area of the dual-phase aerogel-porous carbon sphere composite material provided by the embodiment of the present invention is 200-480 m 2 / g, pore volume 0.085-0.179 cm 3 / g, and an average pore size of 7.9-10.2 nm. Compared with the comparative examples, the aerogel composite material provided by the embodiment of the present invention has a higher specific surface area, a larger pore volume, and a smaller average pore size.
[0040] Adsorption performance verification This embodiment provides the use of the aerogel-porous carbon sphere composite material prepared in the above-mentioned embodiments 1-7 and the aerogel composite material provided in comparative examples 1-8 in the preparation of environmental smoke purification materials. This embodiment uses a multi-component adsorption penetration curve analyzer to evaluate the adsorption performance of nicotine and 3-vinylpyridine by 15 materials prepared in embodiments 1-7 and comparative examples 1-8, so as to prove that the aerogel-porous carbon sphere composite material provided in the embodiment of the present invention can be used as an environmental smoke purification material and can effectively remove environmental smoke. The specific method is as follows: Nicotine evaluation experiment: Weigh about 1 g of purification material sample and fill it into a sample tube with an inner diameter of 10 mm. Purge and activate it with nitrogen at 50°C for 120 min, with a purge gas flow rate of 20 sccm. The experimental conditions were set at room temperature and pressure, the nicotine concentration was set to 55 ppm, the total air flow rate was 80 mL / min, and nitrogen was used as a carrier gas and did not participate in adsorption.
[0041] 3-vinylpyridine evaluation experiment: weigh about 1 g of the purification material sample and fill it into a sample tube with an inner diameter of 10 mm. Purge activation with nitrogen at 50°C for 120 min, with a purge gas flow rate of 20 sccm. The experimental conditions were set at room temperature and pressure, the 3-vinylpyridine concentration was set to 55 ppm, the total inlet flow rate was 80 mL / min, and nitrogen was used as a carrier gas and did not participate in adsorption. The evaluation results are shown in Table 3.
[0042] Table 3 Saturated adsorption of nicotine and 3-vinylpyridine by purification material samples It can be seen from Table 3 that the saturated adsorption amounts of nicotine and 3-vinylpyridine by the purification materials prepared in different embodiments are quite different, and the main reason for this is that their physical and chemical structures are closely related.
[0043] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 1 are 38 mg / g and 28 mg / g, respectively, which are significantly lower than those in Example 1. This is mainly because the amount of sodium polyacrylate used in Comparative Example 1 is lower than that in Example 1, which may result in excessively large pores in the purification material (as shown in Table 2), and excessively fast diffusion of nicotine and 3-vinylpyridine, which is not conducive to the adsorption of nicotine and 3-vinylpyridine, resulting in a decrease in the saturated adsorption amount of nicotine and 3-vinylpyridine.
[0044] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 2 are 47 mg / g and 35 mg / g, respectively, which are significantly lower than those in Example 7. This is mainly because the amount of polyvinyl alcohol used in Comparative Example 2 is higher than that in Example 7, which may result in a smaller pore size of the material and too compact pores, which are not conducive to the diffusion of nicotine and 3-vinylpyridine in the pores of the material, resulting in a decrease in the saturated adsorption amount of nicotine and 3-vinylpyridine.
[0045] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 3 were 49 mg / g and 36 mg / g, respectively, which were significantly lower than those in Example 1. This was mainly because the amount of ferric chloride used in Comparative Example 3 was lower than that in Example 1, which may affect the complexation of iron ions with nicotine and 3-vinylpyridine, resulting in a decrease in the saturated adsorption amounts of nicotine and 3-vinylpyridine.
[0046] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 4 are 50 mg / g and 41 mg / g, respectively, which are significantly lower than those in Example 1. This is mainly because Comparative Example 4 lacks dodder carbon spheres, which results in a lower proportion of carbon spheres in the purification material, and changes in the pore structure in the aerogel, resulting in larger pores, too fast diffusion of nicotine and 3-vinylpyridine, and reduced physical and chemical adsorption properties, resulting in a reduced saturated adsorption amount of nicotine and 3-vinylpyridine.
[0047] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 5 were 25 mg / g and 18 mg / g, respectively, which were significantly lower than those in Example 1. This was mainly because Comparative Example 5 lacked the stir-fried mustard seeds and scutellaria seeds carbon balls, which resulted in a lower proportion of carbon balls in the purification material, and a change in the pore structure in the aerogel, resulting in larger pores, too fast diffusion of nicotine and 3-vinylpyridine, and decreased physical and chemical adsorption properties, resulting in a decrease in the saturated adsorption amount of nicotine and 3-vinylpyridine.
[0048] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 6 are 65 mg / g and 46 mg / g, respectively, which are significantly lower than those in Example 2. This is mainly due to the absence of the second aerogel in the material, which results in too large pores in the purification material, too fast diffusion of nicotine and 3-vinylpyridine, and the lack of metal ions and the second aerogel. These factors combined together cause the physical and chemical adsorption properties of the purification material to decrease, resulting in a decrease in the saturated adsorption amount of nicotine and 3-vinylpyridine.
[0049] The saturated adsorption amounts of nicotine and 3-vinylpyridine in the purification material provided in Comparative Example 7 are 53 mg / g and 31 mg / g, respectively, which are significantly lower than those in Example 2. This is mainly due to the absence of the first aerogel in the material, which results in too large pores in the purification material, too fast diffusion of nicotine and 3-vinylpyridine, and the absence of disodium terephthalate and the first aerogel. These factors combined together cause the physical and chemical adsorption properties of the material to decrease, resulting in a decrease in the saturated adsorption amounts of nicotine and 3-vinylpyridine.
[0050] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 8 were 43 mg / g and 20 mg / g, respectively, which were significantly lower than those in Example 2. This was mainly due to the fact that there were no carbon balls in the material, and the physical and chemical adsorption properties of the material were both reduced, resulting in a decrease in the saturated adsorption amounts of nicotine and 3-vinylpyridine.
[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. An aerogel-porous carbon sphere composite material, characterized in that: The invention comprises porous carbon balls, sodium polyacrylate aerogel and polyvinyl alcohol aerogel, wherein adjacent porous carbon balls are connected by the sodium polyacrylate aerogel and the polyvinyl alcohol aerogel to form pores, the porous carbon balls are mainly composed of carbon balls of scutellaria baicalensis, carbon balls of dodder seeds, carbon balls of mustard seeds and carbon balls of scutellaria baicalensis in a mass ratio of 1.5:(0.5-1.5):(1-2):(0.5-1.5), the sodium polyacrylate aerogel is mainly prepared from terephthalate dicarboxylate and sodium polyacrylate as raw materials, the polyvinyl alcohol aerogel is mainly prepared from metal salt and polyvinyl alcohol as raw materials, and the mass ratio of the porous carbon balls: sodium polyacrylate: terephthalate dicarboxylate: polyvinyl alcohol: metal salt is 100:(10-20):(0.5-1):(10-20):(5-15); Preferably, the specific surface area of the composite material is 200-500 m 2 / g, pore volume 0.08-0.185 cm 3 / g, and the average pore size is 7-10.5 nm.
2. The composite material according to claim 1, characterized in that: The particle sizes of the succulent carbon balls, dodder carbon balls, stir-fried mustard carbon balls and scutellaria carbon balls in the porous carbon balls are 1.7-2.5 mm, 0.8-1.2 mm, 1.2-1.7 mm and 0.2-0.8 mm respectively; Preferably, the porous carbon spheres are composed of Cuscuta carbon spheres with a particle size of 1.8-2.2 mm, Cuscuta carbon spheres with a particle size of 0.8-1.2 mm, Mustard carbon spheres with a particle size of 1.2-1.6 mm, and Lepidium carbon spheres with a particle size of 0.3-0.7 mm, and the mass ratio of the four is 1.5:1.5:1:
1.
3. The composite material according to claim 1 or 2, characterized in that: The terephthalate dicarboxylate is disodium terephthalate, dipotassium terephthalate, disodium terephthalate or 1-sodium formate-4-sodium acetate-benzene.
4. The composite material according to claim 1 or 2, characterized in that: The metal salt is a soluble iron salt, a soluble copper salt or a soluble nickel salt; Preferably, the metal salt is ferric nitrate, copper nitrate, ferric sulfate, copper sulfate, ferric chloride or copper chloride.
5. A method for preparing the composite material according to any one of claims 1 to 4, comprising the steps of: S1. Preparation of a single-phase aerogel-porous carbon sphere composite material: Mix the carbon spheres of Aconitum caryophyllus, the carbon spheres of Cuscuta australis, the carbon spheres of Rhizoma Sinensis, and the carbon spheres of Semen Lepidii evenly and fill the mold, then pour the first gel aqueous solution into the mold until all the carbon spheres therein are just immersed, stand for aging, and freeze-dry to obtain a single-phase aerogel-porous carbon sphere composite material in the mold, wherein: The first gel aqueous solution is an aqueous solution of a uniform mixture of terephthalate and sodium polyacrylate; S2. Preparation of a dual-phase aerogel-porous carbon sphere composite material: pouring a second gel aqueous solution into the mold so that the second gel aqueous solution just completely immerses the single-phase aerogel-porous carbon sphere composite material, allowing it to stand for aging, freeze-drying, and demolding to obtain a dual-phase aerogel-porous carbon sphere composite material; wherein the second gel aqueous solution is an aqueous solution of a uniform mixture of metal salts and polyvinyl alcohol.
6. The preparation method according to claim 5, characterized in that: In the first gel aqueous solution, the percentage concentration of sodium polyacrylate is 5%-10%, and the mass percentage concentration of terephthalate dicarboxylate is 0.25-0.5%; Preferably, the mass ratio of the first gel aqueous solution to the carbon spheres therein is (1.8-2.2): 1; Preferably, the molecular weight of the sodium polyacrylate is 2-3 million.
7. The preparation method according to claim 5 or 6, characterized in that: In the second gel aqueous solution, the concentration of polyvinyl alcohol is 5.5%-10%, and the mass concentration of metal salt is 3%-8.5%; Preferably, the mass percentage concentration of the metal salt is 6%-7.5%; Preferably, the mass ratio of the second gel aqueous solution to the carbon spheres therein is (1.75-1.90): 1 Preferably, the polyvinyl alcohol is polyvinyl alcohol 0588.
8. Use of the composite material according to any one of claims 1 to 4 in preparing a nicotine adsorption material; Preferably, the minimum saturated adsorption capacity of nicotine by 1 g of the composite material is 60 mg / g; More preferably, the saturated adsorption capacity of nicotine by 1 g of the composite material is 65 to 280 mg / g.
9. Use of the composite material according to any one of claims 1 to 4 in the preparation of 3-vinylpyridine adsorption material; Preferably, the minimum saturated adsorption capacity of 3-vinylpyridine by 1 g of the composite material is 50 mg / g; More preferably, the saturated adsorption capacity of 3-vinylpyridine by 1 g of the composite material is 55 to 230 mg / g.
10. Use of the composite material according to any one of claims 1 to 4 in preparing an environmental flue gas purification material; Preferably, the minimum saturated adsorption capacity of nicotine and 3-vinylpyridine by 1 g of the composite material is 60 mg / g and 50 mg / g, respectively; More preferably, the saturated adsorption capacity of nicotine and 3-vinylpyridine per 1 g of the composite material is 65-280 mg / g and 55-230 mg / g, respectively.
